2018
DOI: 10.1111/birt.12377
|View full text |Cite
|
Sign up to set email alerts
|

Workplace support and breastfeeding duration: The mediating effect of breastfeeding intention and self‐efficacy

Abstract: Self-efficacy is an important predictor for breastfeeding duration. Workplaces may help bolster women's self-efficacy by providing environments that are supportive to breastfeeding working mothers. Future research is needed to identify breastfeeding policies that boost self-efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 32 publications
3
33
0
4
Order By: Relevance
“…The key barriers for employed mothers to continue breastfeeding include privacy issues, low support from their workplace, fatigue, lack of break time to express milk, inflexible work schedules, and inadequate facilities for pumping and storing milk [ 40 , 45 , 46 ]. Studies have suggested that breastfeeding-friendly workplaces increase the rate of breastfeeding duration among mothers who return to work postpartum [ 45 , 47 ]. Hence, health-promotion policies with effective translation around breastfeeding-friendly workplaces could significantly affect breastfeeding duration.…”
Section: Discussionmentioning
confidence: 99%
“…The key barriers for employed mothers to continue breastfeeding include privacy issues, low support from their workplace, fatigue, lack of break time to express milk, inflexible work schedules, and inadequate facilities for pumping and storing milk [ 40 , 45 , 46 ]. Studies have suggested that breastfeeding-friendly workplaces increase the rate of breastfeeding duration among mothers who return to work postpartum [ 45 , 47 ]. Hence, health-promotion policies with effective translation around breastfeeding-friendly workplaces could significantly affect breastfeeding duration.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding problems are common, affecting between 20%-80% of women (Cooklin et al, 2018). These problems may interfere with breastfeeding self-efficacy, a factor linked to breastfeeding duration (Franco-Antonio et al, 2019;Wallenborn et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Araştırmalar, süt salınımından sorumlu ana hormon olan oksitosinin stres durumunda engellendiğini göstermektedir. 39 İşveren, amirler, sendika ve iş arkadaşlarının rolünün, kadının iş ve aile ihtiyaçlarını dengelemesinde etkili olduğu, destekleyici davranışların stresi azaltarak emzirme uygulamaları üzerinde pozitif bir etki oluşturduğu ifade edilmektedir 31 . Ayrıca çalışan annelerin emzirme uygulamalarında, aileden alınan sosyal ve duygusal desteğin önemli bir rolü olduğu vurgulanmaktadır.…”
Section: Discussionunclassified